What does it mean to “grasp the rectangle”? Organization of linguistic formulation and activation of argumentative processes in geometrical problems - Bolondi, Giorgio; Branchetti, Laura; Cascella, Clelia; Giberti, Chiara (Frontiers in Education, 2023)
The purpose of this paper is to explore whether and how the verbal formulation of a task influences the activation of argumentative processes in a geometrical word problem involving figural concepts. The study adopts a multilevel explanatory mixed methods research design. Both the quantitative and qualitative experiments were based on a paradigmatic situation of figural concept proposed by Fischbein. Our main quantitative result is that different formulations of a task impact on students' performance and on the selection of an argumentative or operational option. Moreover, we qualitatively investigated the students' approaches, and this allowed to observe a variety of approaches ranging from a completely operational one to an argumentative one. The analysis highlighted interesting facts about the integration of sentential information and diagrams and the students' strategies.